Recent advances in the asymmetric phosphoric acid-catalyzed synthesis of axially chiral compounds - Woldegiorgis, Alemayehu Gashaw; Lin, Xufeng (Beilstein Journal of Organic Chemistry, 2021)
In recent years, the synthesis of axially chiral compounds has received considerable attention due to their extensive application as biologically active compounds in medicinal chemistry and as chiral ligands in asymmetric catalysis. Chiral phosphoric acids are recognized as efficient organocatalysts for a variety of enantioselective transformations. In this review, we summarize the recent development of chiral phosphoric acid-catalyzed synthesis of a wide range of axially chiral biaryls, heterobiaryls, vinylarenes, N-arylamines, spiranes, and allenes with high efficiency and excellent stereoselectivity.
Keywords: allenes; atropisomerism; axial chirality; chiral phosphoric acid; heterobiaryls; spiranes

(untitled) - Bao, X.; Rodriguez, J.; Bonne, D. (Angew. Chem., Int. Ed., 2020)

(untitled) - Bai, H.-Y.; Tan, F.-X.; Liu, T.-Q.; Zhu, G.-D.; Tian, J.-M.; Ding, T.-M.; Chen, Z.-M.; Zhang, S.-Y. (Nat. Commun., 2019)

(untitled) - Kumarasamy, E.; Raghunathan, R.; Sibi, M. P.; Sivaguru, J. (Chem. Rev., 2015)

(untitled) - Pinxterhuis, E. B.; Gualtierotti, J.-B.; Heeres, H. J.; de Vries, J. G.; Feringa, B. L. (Chem. Sci., 2017)

(untitled) - Shirakawa, S.; Liu, S.; Kaneko, S. (Chem. – Asian J., 2016)

(untitled) - Di Iorio, N.; Crotti, S.; Bencivenni, G. (Chem. Rec., 2019)

(untitled) - Hu, Y.-L.; Wang, Z.; Yang, H.; Chen, J.; Wu, Z.-B.; Lei, Y.; Zhou, L. (Chem. Sci., 2019)

(untitled) - Carmona, J. A.; Rodríguez-Franco, C.; Fernández, R.; Hornillos, V.; Lassaletta, J. M. (Chem. Soc. Rev., 2021)

(untitled) - Kitagawa, O. (Acc. Chem. Res., 2021)

(untitled) - Liao, G.; Zhou, T.; Yao, Q.-J.; Shi, B.-F. (Chem. Commun., 2019)

(untitled) - Renzi, P. (Org. Biomol. Chem., 2017)

(untitled) - Loxq, P.; Manoury, E.; Poli, R.; Deydier, E.; Labande, A. (Coord. Chem. Rev., 2016)

(untitled) - Da, B.-C.; Xiang, S.-H.; Li, S.; Tan, B. (Chin. J. Chem., 2021)

(untitled) - Wang, Y.-B.; Tan, B. (Acc. Chem. Res., 2018)

(untitled) - Akiyama, T.; Mori, K. (Chem. Rev., 2015)

(untitled) - Bringmann, G.; Price Mortimer, A. J.; Keller, P. A.; Gresser, M. J.; Garner, J.; Breuning, M. (Angew. Chem., Int. Ed., 2005)

(untitled) - Li, S.; Zhang, J.-W.; Li, X.-L.; Cheng, D.-J.; Tan, B. (J. Am. Chem. Soc., 2016)

(untitled) - Liu, Y.; Tse, Y.-L. S.; Kwong, F. Y.; Yeung, Y.-Y. (ACS Catal., 2017)

(untitled) - Tian, M.; Bai, D.; Zheng, G.; Chang, J.; Li, X. (J. Am. Chem. Soc., 2019)

(untitled) - Cho, H.; Choi, M.-K.; Cho, D.-Y.; Yeo, C.-W.; Jeong, H.-E.; Shon, J.-H.; Lee, J.-Y.; Shin, J.-S.; Cho, M.; Kim, D.-Y.; Shin, J.-G. (J. Clin. Pharmacol., 2012)

(untitled) - Zhang, L.; Xiang, S.-H.; Wang, J. (Joelle).; Xiao, J.; Wang, J.-Q.; Tan, B. (Nat. Commun., 2019)

(untitled) - Yang, G.; Guo, D.; Meng, D.; Wang, J. (Nat. Commun., 2019)

(untitled) - Wang, J.-Z.; Zhou, J.; Xu, C.; Sun, H.; Kürti, L.; Xu, Q.-L. (J. Am. Chem. Soc., 2016)

(untitled) - Qi, L.-W.; Li, S.; Xiang, S.-H.; Wang, J. (Joelle).; Tan, B. (Nat. Catal., 2019)

(untitled) - Zhou, Y.; Xia, Z.-L.; Gu, Q.; You, S.-L. (Org. Lett., 2017)

(untitled) - Qian, D.; Wu, L.; Lin, Z.; Sun, J. (Nat. Commun., 2017)

(untitled) - Ogasawara, M. (Tetrahedron: Asymmetry, 2009)

(untitled) - Shao, Y.-D.; Cheng, D.-J. (ChemCatChem, 2021)

(untitled) - Maji, R.; Mallojjala, S. C.; Wheeler, S. E. (Chem. Soc. Rev., 2018)

(untitled) - Xia, Z.-L.; Xu-Xu, Q.-F.; Zheng, C.; You, S.-L. (Chem. Soc. Rev., 2020)

(untitled) - Akiyama, T.; Itoh, J.; Yokota, K.; Fuchibe, K. (Angew. Chem., Int. Ed., 2004)

(untitled) - Xiao, Y.; Sun, Z.; Guo, H.; Kwon, O. (Beilstein J. Org. Chem., 2014)

(untitled) - Xu, F.; Huang, D.; Han, C.; Shen, W.; Lin, X.; Wang, Y. (J. Org. Chem., 2010)

(untitled) - Isaac, K.; Stemper, J.; Servajean, V.; Retailleau, P.; Pastor, J.; Frison, G.; Kaupmees, K.; Leito, I.; Betzer, J.-F.; Marinetti, A. (J. Org. Chem., 2014)

(untitled) - Wang, Y.-B.; Zheng, S.-C.; Hu, Y.-M.; Tan, B. (Nat. Commun., 2017)

(untitled) - Chen, Y.-H.; Cheng, D.-J.; Zhang, J.; Wang, Y.; Liu, X.-Y.; Tan, B. (J. Am. Chem. Soc., 2015)

(untitled) - Nguyen, T. T. (Org. Biomol. Chem., 2019)

(untitled) - Wang, L.; Zhong, J.; Lin, X. (Angew. Chem., Int. Ed., 2019)

(untitled) - Dherbassy, Q.; Djukic, J.-P.; Wencel‐Delord, J.; Colobert, F. (Angew. Chem., Int. Ed., 2018)

(untitled) - Smrčina, M.; Lorenc, M.; Hanuš, V.; Kočovský, P. (Synlett, 1991)

(untitled) - Li, G.-Q.; Gao, H.; Keene, C.; Devonas, M.; Ess, D. H.; Kürti, L. (J. Am. Chem. Soc., 2013)

(untitled) - Chen, Y.-H.; Qi, L.-W.; Fang, F.; Tan, B. (Angew. Chem., Int. Ed., 2017)

(untitled) - Mori, K.; Ichikawa, Y.; Kobayashi, M.; Shibata, Y.; Yamanaka, M.; Akiyama, T. (J. Am. Chem. Soc., 2013)

(untitled) - Clayden, J.; Moran, W. J.; Edwards, P. J.; LaPlante, S. R. (Angew. Chem., Int. Ed., 2009)

(untitled) - Wang, C.-S.; Li, T.-Z.; Liu, S.-J.; Zhang, Y.-C.; Deng, S.; Jiao, Y.; Shi, F. (Chin. J. Chem., 2020)

(untitled) - Luo, J.; Zhang, T.; Wang, L.; Liao, G.; Yao, Q.-J.; Wu, Y.-J.; Zhan, B.-B.; Lan, Y.; Lin, X.-F.; Shi, B.-F. (Angew. Chem., Int. Ed., 2019)

(untitled) - Uraguchi, D.; Terada, M. (J. Am. Chem. Soc., 2004)

(untitled) - Parmar, D.; Sugiono, E.; Raja, S.; Rueping, M. (Chem. Rev., 2014)

(untitled) - Terada, M. (Chem. Commun., 2008)

(untitled) - Zhan, B.-B.; Wang, L.; Luo, J.; Lin, X.-F.; Shi, B.-F. (Angew. Chem., Int. Ed., 2020)

(untitled) - Zhan, B.-B.; Jia, Z.-S.; Luo, J.; Jin, L.; Lin, X.-F.; Shi, B.-F. (Org. Lett., 2020)

(untitled) - Zhang, H.-H.; Wang, C.-S.; Li, C.; Mei, G.-J.; Li, Y.; Shi, F. (Angew. Chem., Int. Ed., 2017)

(untitled) - Lu, D.-L.; Chen, Y.-H.; Xiang, S.-H.; Yu, P.; Tan, B.; Li, S. (Org. Lett., 2019)

(untitled) - He, C.; Hou, M.; Zhu, Z.; Gu, Z. (ACS Catal., 2017)

(untitled) - Ito, C.; Thoyama, Y.; Omura, M.; Kajiura, I.; Furukawa, H. (Chem. Pharm. Bull., 1993)

(untitled) - Bringmann, G.; Tasler, S.; Endress, H.; Kraus, J.; Messer, K.; Wohlfarth, M.; Lobin, W. (J. Am. Chem. Soc., 2001)

(untitled) - Li, B.-J.; Yang, S.-D.; Shi, Z.-J. (Synlett, 2008)

(untitled) - Qin, Y.; Zhu, L.; Luo, S. (Chem. Rev., 2017)

(untitled) - Qi, L.-W.; Mao, J.-H.; Zhang, J.; Tan, B. (Nat. Chem., 2018)

(untitled) - Zheng, S.-C.; Wang, Q.; Zhu, J. (Angew. Chem., Int. Ed., 2019)

(untitled) - Ding, W.-Y.; Yu, P.; An, Q.-J.; Bay, K. L.; Xiang, S.-H.; Li, S.; Chen, Y.; Houk, K. N.; Tan, B. (Chem, 2020)

(untitled) - Anilkumar, G. N.; Lesburg, C. A.; Selyutin, O.; Rosenblum, S. B.; Zeng, Q.; Jiang, Y.; Chan, T.-Y.; Pu, H.; Vaccaro, H.; Wang, L.; Bennett, F.; Chen, K. X.; et al. (Bioorg. Med. Chem. Lett., 2011)

(untitled) - Jiang, F.; Luo, G.-Z.; Zhu, Z.-Q.; Wang, C.-S.; Mei, G.-J.; Shi, F. (J. Org. Chem., 2018)

(untitled) - Li, T.-Z.; Liu, S.-J.; Tan, W.; Shi, F. (Chem. – Eur. J., 2020)

(untitled) - Jiang, F.; Chen, K.-W.; Wu, P.; Zhang, Y.-C.; Jiao, Y.; Shi, F. (Angew. Chem., Int. Ed., 2019)

(untitled) - Ma, C.; Jiang, F.; Sheng, F.-T.; Jiao, Y.; Mei, G.-J.; Shi, F. (Angew. Chem., Int. Ed., 2019)

(untitled) - Sheng, F.-T.; Li, Z.-M.; Zhang, Y.-Z.; Sun, L.-X.; Zhang, Y.-C.; Tan, W.; Shi, F. (Chin. J. Chem., 2020)

(untitled) - Chen, K.-W.; Wang, Z.-S.; Wu, P.; Yan, X.-Y.; Zhang, S.; Zhang, Y.-C.; Shi, F. (J. Org. Chem., 2020)

(untitled) - Chauhan, P.; Mahajan, S.; Enders, D. (Chem. Commun., 2015)

(untitled) - Yuan, H.; Li, Y.; Zhao, H.; Yang, Z.; Li, X.; Li, W. (Chem. Commun., 2019)

(untitled) - Horton, D. A.; Bourne, G. T.; Smythe, M. L. (Chem. Rev., 2003)

(untitled) - Liaw, D.-J.; Wang, K.-L.; Huang, Y.-C.; Lee, K.-R.; Lai, J.-Y.; Ha, C.-S. (Prog. Polym. Sci., 2012)

(untitled) - Xia, W.; An, Q.-J.; Xiang, S.-H.; Li, S.; Wang, Y.-B.; Tan, B. (Angew. Chem., Int. Ed., 2020)

(untitled) - Bao, X.; Rodriguez, J.; Bonne, D. (Chem. Sci., 2020)

(untitled) - Taylor, R. D.; MacCoss, M.; Lawson, A. D. G. (J. Med. Chem., 2014)

(untitled) - Zhou, C.; Hassner, A. (Carbohydr. Res., 2001)

(untitled) - Kwon, Y.; Li, J.; Reid, J. P.; Crawford, J. M.; Jacob, R.; Sigman, M. S.; Toste, F. D.; Miller, S. J. (J. Am. Chem. Soc., 2019)

(untitled) - Man, N.; Lou, Z.; Li, Y.; Yang, H.; Zhao, Y.; Fu, H. (Org. Lett., 2020)

(untitled) - Hughes, C. C.; Prieto-Davo, A.; Jensen, P. R.; Fenical, W. (Org. Lett., 2008)

(untitled) - Liu, J.; Li, H.; Spannenberg, A.; Franke, R.; Jackstell, R.; Beller, M. (Angew. Chem., Int. Ed., 2016)

(untitled) - Faigl, F.; Mátravölgyi, B.; Holczbauer, T.; Czugler, M.; Madarász, J. (Tetrahedron: Asymmetry, 2011)

(untitled) - Zhang, L.; Zhang, J.; Ma, J.; Cheng, D.-J.; Tan, B. (J. Am. Chem. Soc., 2017)

(untitled) - Dai, X.; Wong, A.; Virgil, S. C. (J. Org. Chem., 1998)

(untitled) - Michael, J. P. (Nat. Prod. Rep., 2002)

(untitled) - Shao, Y.-D.; Dong, M.-M.; Wang, Y.-A.; Cheng, P.-M.; Wang, T.; Cheng, D.-J. (Org. Lett., 2019)

(untitled) - Bisag, G. D.; Pecorari, D.; Mazzanti, A.; Bernardi, L.; Fochi, M.; Bencivenni, G.; Bertuzzi, G.; Corti, V. (Chem. – Eur. J., 2019)

(untitled) - Ros, A.; Estepa, B.; Ramírez-López, P.; Álvarez, E.; Fernández, R.; Lassaletta, J. M. (J. Am. Chem. Soc., 2013)

(untitled) - Armstrong, R. J.; Smith, M. D. (Angew. Chem., Int. Ed., 2014)

(untitled) - Gao, D.-W.; Gu, Q.; You, S.-L. (ACS Catal., 2014)

(untitled) - Baker, R. W.; Hambley, T. W.; Turner, P.; Wallace, B. J. (Chem. Commun., 1996)

(untitled) - Hattori, T.; Date, M.; Sakurai, K.; Morohashi, N.; Kosugi, H.; Miyano, S. (Tetrahedron Lett., 2001)

(untitled) - Ma, C.; Sheng, F.-T.; Wang, H.-Q.; Deng, S.; Zhang, Y.-C.; Jiao, Y.; Tan, W.; Shi, F. (J. Am. Chem. Soc., 2020)

(untitled) - Kitagawa, O.; Takahashi, M.; Yoshikawa, M.; Taguchi, T. (J. Am. Chem. Soc., 2005)

(untitled) - Zhang, J.-W.; Xu, J.-H.; Cheng, D.-J.; Shi, C.; Liu, X.-Y.; Tan, B. (Nat. Commun., 2016)

(untitled) - Koelblinger, P.; Dornbierer, J.; Dummer, R. (Future Oncol., 2017)

(untitled) - Liu, Q.; Sabnis, Y.; Zhao, Z.; Zhang, T.; Buhrlage, S. J.; Jones, L. H.; Gray, N. S. (Chem. Biol., 2013)

(untitled) - Vaidya, S. D.; Toenjes, S. T.; Yamamoto, N.; Maddox, S. M.; Gustafson, J. L. (J. Am. Chem. Soc., 2020)

(untitled) - Franz, A. K.; Hanhan, N. V.; Ball-Jones, N. R. (ACS Catal., 2013)

(untitled) - Kita, Y.; Higuchi, K.; Yoshida, Y.; Iio, K.; Kitagaki, S.; Ueda, K.; Akai, S.; Fujioka, H. (J. Am. Chem. Soc., 2001)

(untitled) - Xie, J.-H.; Zhou, Q.-L. (Acc. Chem. Res., 2008)

(untitled) - Hoffmann-Röder, A.; Krause, N. (Angew. Chem., Int. Ed., 2004)

(untitled) - Ye, J.; Ma, S. (Org. Chem. Front., 2014)

(untitled) - Yang, J.; Wang, Z.; He, Z.; Li, G.; Hong, L.; Sun, W.; Wang, R. (Angew. Chem., Int. Ed., 2020)

(untitled) - Li, F.; Liang, S.; Luan, Y.; Chen, X.; Zhao, H.; Huang, A.; Li, P.; Li, W. (Org. Chem. Front., 2021)

(untitled) - Zhu, W.-R.; Su, Q.; Diao, H.-J.; Wang, E.-X.; Wu, F.; Zhao, Y.-L.; Weng, J.; Lu, G. (Org. Lett., 2020)

(untitled) - Zhang, P.; Huang, Q.; Cheng, Y.; Li, R.; Li, P.; Li, W. (Org. Lett., 2019)

(untitled) - Woldegiorgis, A. G.; Han, Z.; Lin, X. (Org. Lett., 2021)